KULTURA W PODRĘCZNIKACH DO NAUKI JĘZYKÓW OBCYCH JAKO CZYNNIK WPŁYWAJĄCY NA ROZWÓJ MIĘDZYKULTUROWEJ KOMPETENCJI KOMUNIKACYJNEJ - Piwowarczyk, Anna Jadwiga (Neofilolog, 2018)
Enriching the knowledge on culture seems to be a logical consequence of the development of intercultural communication competence. The aim of this article is to evaluate cultural content embedded in selected textbooks used in foreign language courses. The textbooks were analysed by means of a questionnaire based on Hofstede model and CEF guidelines.